VANCOMYCIN-RESISTANT ENTEROCOCCI (VRE) AND THE ROLE OF THE HEALTHCARE WORKER - Ott, Marilyn; Wirick, Heather (Operating Room Nurses Association of Canada Journal, 2008)
Antibiotic resistance has increased dramatically within the last decade. The spread of antibiotic resistant strains of bacteria has become a threat within hospitals. Vancomycin-resistant enterococci (VRE) has emerged as one of these strains. VRE is a robust microorganism and can survive for long periods of time on environmental surfaces. VRE spreads quickly from patient to patient through contact with health care workers. This strain can increase the mortality rate in immuno-compromised patients. Hospital health care workers have an important role to play in the prevention and control of VRE. Proper, and frequent, hand-washing significantly contribute to preventing and controlling the spread of VRE. Providing health care workers with education and resources is also a key factor. The health belief model helps to explain how to approach and implement changes to practice.